Two-component fast-curing adhesive for flange rubber joint and preparation method thereof
Patent Information
- Application Number
- CN202611132371.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-29
AI Technical Summary
然而,微胶囊破裂后壳层碎片以惰性异物残留于胶层,与环氧基体相容性差,在外载荷和热应力作用下成为优先的应力集中和裂纹萌生点;增韧剂的引入会降低固化物玻璃化转变温度,损害高温持载能力;且刚性填料与环氧基体间仅为物理嵌合,热循环过程中因膨胀系数差异导致的界面脱粘难以避免,脱粘形成的微孔洞进一步削弱了胶层的导热性和完整性
[0018]Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention discloses a two-component fast-curing adhesive for flange assembly and its preparation method. The adhesive includes component A and component B. In component A, the composite thermally conductive filler has a core-shell structure with a spherical α-alumina core and an acrylate copolymer containing carboxyl and epoxy groups as the shell, which is used to provide an efficient thermal conductivity path and chemically bond with the epoxy group. In component B, the microcapsule curing agent has a multi-level core-shell structure of core curing agent/polyurea wall layer/polydopamine-metal ion shell, which is used to achieve long-term isolated storage of curing agent and epoxy resin and rapid release and catalytic curing during application.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of epoxy adhesive technology, and more particularly to a two-component fast-curing adhesive for flange fitting and its preparation method. Background Technology
[0002] Flange connections are a crucial method for sealing and assembling pipelines and containers in industries such as petrochemicals, shipbuilding, power, and nuclear power. Compared to mechanical gaskets, adhesive seals offer advantages such as uniform stress distribution, high sealing reliability, and good vibration resistance. However, they impose several stringent requirements on adhesive performance: they must cure quickly after assembly and fastening to meet production needs; they must maintain bond strength without diminishing under repeated temperature cycles; and they must provide reliable adhesion and protection for various flange materials, including carbon steel, stainless steel, and aluminum alloys.
[0003] To address the aforementioned issues, existing solutions include: encapsulating curing agents in microcapsules using polyurea or similar materials, releasing them under pressure to balance latency and rapid curing; adding liquid rubber or core-shell rubber for toughening to improve the crack resistance of highly filled systems; and introducing thermally conductive fillers to reduce the coefficient of thermal expansion and improve thermal conductivity. However, after microcapsule rupture, shell fragments remain as inert foreign matter in the adhesive layer, exhibiting poor compatibility with the epoxy matrix. Under external loads and thermal stress, these fragments become preferred stress concentration points and crack initiation sites. The introduction of toughening agents lowers the glass transition temperature of the cured product, impairing its high-temperature load-bearing capacity. Furthermore, the rigid filler and epoxy matrix are only physically interlocked, making interfacial debonding due to differences in expansion coefficients during thermal cycling unavoidable. The resulting micropores further weaken the thermal conductivity and integrity of the adhesive layer. More importantly, each of these solutions addresses a single problem independently, lacking chemical-level functional coupling within the same system. Consequently, the overall performance is insufficient to meet the long-term performance requirements of flanges under harsh operating conditions. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art by proposing a two-component fast-curing adhesive for flange assembly and its preparation method.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: a two-component, fast-curing adhesive for flange assembly, comprising component A and component B, in parts by weight: The A component comprises: 100 parts of bisphenol A type epoxy resin, 15 parts of diluent, 16 parts of polyurethane toughening agent, 140-200 parts of composite thermally conductive filler, 2 parts of silane coupling agent, and 2 parts of fumed silica.
[0006] The composite thermally conductive filler has a core-shell structure with spherical α-alumina as the core and an acrylate copolymer containing carboxyl and epoxy groups as the shell. Polymerizable double bonds are anchored on the alumina surface using a silane coupling agent, followed by emulsion polymerization to copolymerize methacrylic acid, butyl acrylate, and glycidyl methacrylate on the alumina surface, forming a polymer shell through covalent grafting. This filler exhibits both high thermal conductivity and excellent matrix compatibility. The carboxyl groups in the shell can participate in the ring-opening reaction of the epoxy groups, and the epoxy groups can crosslink with the curing agent, allowing the filler to be chemically bonded into the epoxy network, significantly reducing interfacial thermal resistance.
[0007] Component B comprises: 50-65 parts of microcapsule curing agent, 12 parts of diluent, and 1 part of fumed silica.
[0008] The microcapsule curing agent has a multi-layered core-shell structure: its core is cashew phenol amine, its inner wall material is a polyurea layer formed by the reaction of hexamethylene diisocyanate and amine groups at the interface, and its outermost layer is a polydopamine coating complexed with metal ions; the metal ions are zirconium ions or zinc ions, complexed on the catechol groups of the polydopamine layer. This microcapsule curing agent remains intact during adhesive mixing and application. Under pressure or shear force, the capsule wall ruptures, releasing the curing agent. Simultaneously, the metal ions catalyze the ring-opening polymerization of epoxy groups, achieving rapid curing. The catechol groups of the polydopamine layer can also form coordination bonds with the metal substrate, improving adhesive strength.
[0009] The preparation method of the two-component fast-curing flange adhesive includes the following steps: Step S1: Add bisphenol A type epoxy resin, diluent, polyurethane toughening agent and silane coupling agent to a kneader, stir and knead for 30 min at 70℃ and vacuum degree of -0.08 MPa; then add composite thermally conductive filler, knead at 80℃ for 90 min; after discharge, grind, then add fumed silica, and degas under vacuum for 30 min to obtain component A.
[0010] Step S2: Combine the microcapsule curing agent, diluent and fumed silica and stir for 30 min, then vacuum degas for 15 min to obtain component B. During the stirring process, control the material temperature to not exceed 35℃.
[0011] The composite thermally conductive filler is prepared by the following steps: Step A1: Spherical α-alumina with an average particle size of 5 μm and spherical α-alumina with an average particle size of 30 μm are mixed at a mass ratio of 1:1 and ultrasonically dispersed in a 95% (v / v) aqueous ethanol solution. γ-methacryloyloxypropyltrimethoxysilane is added, and the pH is adjusted to 4.0 with acetic acid. The mixture is stirred at 60°C for 4 h, filtered, washed with ethanol, and vacuum dried at 80°C to obtain surface-grafted alumina powder. Furthermore, in step A1, the ratio of the total mass of alumina, γ-methacryloxypropyltrimethoxysilane, and aqueous ethanol solution is 100g:3g:300mL.
[0012] Step A2: Sodium dodecyl sulfate, surface-grafted alumina powder and deionized water are mixed, ultrasonically dispersed and heated to 80°C. Then a mixture of methacrylic acid, butyl acrylate, glycidyl methacrylate and ammonium persulfate is added. The mixture is reacted for 2 h, cooled to room temperature, demulsified, filtered, washed with deionized water and vacuum dried at 60°C to obtain the composite thermally conductive filler. Furthermore, in step A2, the ratio of sodium dodecyl sulfate, surface-grafted alumina powder, deionized water, methacrylic acid, butyl acrylate, glycidyl methacrylate, and ammonium persulfate is 0.8g:80g:150mL:5-8g:10-16g:2g:0.2g.
[0013] The microcapsule curing agent is prepared by the following steps: Step B1: Mix cashew phenol and isophorone diamine, stir at 80°C and add paraformaldehyde, heat to 95°C and react for 3 hours, then distill under reduced pressure at 120°C to obtain cashew phenol aldehyde amine curing agent. Furthermore, in step B1, during the preparation of the cashew phenol amine curing agent, the ratio of cashew phenol, isophorone diamine, and paraformaldehyde is 10g:1.1g:7.2g.
[0014] Step B2: Span-85 and liquid paraffin were mixed and stirred at 400 rpm for 15 min at room temperature. Cashew phenol amine curing agent and methyl p-toluenesulfonate were then added and emulsified at 1200 rpm for 10 min to obtain an emulsion. Hexamethylene diisocyanate was mixed with liquid paraffin and stirred at 300 rpm for 10 min at room temperature to obtain a mixture. The mixture was added dropwise to the emulsion and reacted at room temperature for 1 h. The temperature was then raised to 55 °C and the reaction continued for 5 h. The mixture was washed with cyclohexane and air-dried to obtain polyurea microcapsules. Furthermore, in step B2: during the emulsion preparation process, the ratio of Span-85, liquid paraffin, cashew phenol amine curing agent, and methyl p-toluenesulfonate is 1.5g:50g:4-5g:0.05g; during the mixture preparation process, the ratio of hexamethylene diisocyanate to liquid paraffin is 1g:2.5g. Step B3: Disperse polyurea microcapsules ultrasonically in dopamine hydrochloride solution, stir at room temperature and 120 rpm for 12 h, filter, wash with deionized water, and dry to obtain polydopamine-coated microcapsules; immerse the polydopamine-coated microcapsules in a metal ion solution, stir at room temperature for 2 h, wash with deionized water, and dry to obtain microcapsule curing agent. Further, in step B3: the dopamine hydrochloride solution has a mass concentration of 2 g / L and a pH of 8.5; the metal ion solution is either a zinc ion solution or a zirconium ion solution. When a zirconium ion solution is used, the concentration is 0.15 mol / L of zirconium oxychloride octahydrate aqueous solution with a pH of 4; when a zinc ion solution is used, the concentration is 0.18 mol / L of zinc acetate aqueous solution.
[0015] Furthermore, in step A above: γ-methacryloxypropyltrimethoxysilane, under acetic acid catalysis, undergoes methoxy hydrolysis to form silanol groups, which condense with hydroxyl groups on the alumina surface, anchoring the methacryloxy groups on the alumina surface via Si-O-Al covalent bonds. This modification transforms the alumina from hydrophilic to lipophilic, giving it polymerizable double-bonded functional groups on the surface, providing grafting sites for subsequent emulsion polymerization. Meanwhile, ammonium persulfate decomposes at 80°C to generate free radicals, initiating a copolymerization reaction between the anchored methacryloxy double bonds on the alumina surface and methacrylic acid, butyl acrylate, and glycidyl methacrylate in the solution. The copolymer chains grow from the alumina surface via covalent bonds, forming a polymer shell of uniform thickness. Methacrylic acid provides carboxyl groups; butyl acrylate provides flexible segments, giving the shell elastomer characteristics and the ability to absorb interfacial stress; and glycidyl methacrylate provides epoxy groups, participating in the curing and crosslinking reaction. By combining large and small-sized alumina particles, the small particles fill the gaps between the large particles, creating a denser heat conduction path and further improving heat conduction efficiency.
[0016] In step B above: First, the active hydrogen on the benzene ring of cashew phenol undergoes a Mannich condensation reaction with formaldehyde and the primary amino group of isophorone diamine produced by the depolymerization of paraformaldehyde under heating conditions, generating a cashew phenol aldehyde amine compound containing aminomethyl groups. This curing agent molecule simultaneously contains phenolic hydroxyl groups, secondary amino groups, and flexible long-chain alkyl groups, exhibiting both high reactivity and good flexibility. Span-85 is used as an emulsifier to uniformly disperse the cashew phenol aldehyde amine curing agent droplets in the continuous liquid paraffin phase. Methyl p-toluenesulfonate, as a potential catalyst, dissolves in the curing agent droplets. When a liquid paraffin solution of hexamethylene diisocyanate is added to the emulsion, hexamethylene diisocyanate diffuses to the droplet interface and undergoes a condensation reaction with the amino groups (-NH2, -NH-) in the curing agent, generating a polyurea wall layer. This wall layer encapsulates the curing agent and methyl p-toluenesulfonate together in the core. The microcapsules are then immersed in a dopamine solution. Under weakly alkaline conditions (pH 8.5), dopamine undergoes self-polymerization, depositing a polydopamine coating on the surface of the polyurea microcapsules. The polydopamine chains contain abundant catechol and amine groups, providing numerous active chelating sites on the microcapsule surface. When the polydopamine-coated microcapsules are immersed in zirconium or zinc solutions, metal ions form stable five-membered chelate rings with two adjacent phenolic hydroxyl groups on the catechol groups, firmly complexing the microcapsule surface. These complexed metal ions act as Lewis acid catalysts, accelerating the ring-opening polymerization of epoxy groups after the microcapsules rupture and release the curing agent, thus significantly increasing the curing speed. Simultaneously, the catechol groups in the polydopamine layer exhibit strong coordination adhesion to the metal substrate, further enhancing the adhesive strength to the flange.
[0017] Furthermore, in component A, bisphenol A type epoxy resin provides the main adhesive strength and heat resistance; the diluent reduces the system viscosity and improves the sizing processability; the polyurethane toughening agent forms an island structure in the epoxy network to dissipate stress, achieving high toughness over a wide temperature range; the composite thermally conductive filler provides a high thermal conductivity pathway, and the carboxyl and epoxy groups in its shell enable it to chemically bond and embed into the epoxy cross-linking network, eliminating the weak interface layer between the traditional filler and the matrix, thus simultaneously improving thermal conductivity and mechanical strength; the silane coupling agent further improves filler dispersion and interfacial bonding; fumed silica prevents filler sedimentation during storage. In component B, the microcapsule curing agent is the core functional unit, and its multi-level core-shell structure endows it with multiple functions of isolated storage, rapid release, and catalytic acceleration; the diluent adjusts the viscosity of component B. After components A and B are mixed, the microcapsules rupture under the action of sizing pressure and shear force, and the core curing agent and catalyst are released simultaneously. Metal ions catalyze the rapid ring-opening of epoxy groups, achieving rapid curing at room temperature, meeting the production requirements of flange adhesive fitting.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention discloses a two-component fast-curing adhesive for flange assembly and its preparation method. The adhesive includes component A and component B. In component A, the composite thermally conductive filler has a core-shell structure with a spherical α-alumina core and an acrylate copolymer containing carboxyl and epoxy groups as the shell, which is used to provide an efficient thermal conductivity path and chemically bond with the epoxy group. In component B, the microcapsule curing agent has a multi-level core-shell structure of core curing agent / polyurea wall layer / polydopamine-metal ion shell, which is used to achieve long-term isolated storage of curing agent and epoxy resin and rapid release and catalytic curing during application.
[0019] This invention employs a strategy combining silane modification, emulsion polymerization grafting, and large / small particle size blending to form a covalently bonded elastomeric shell on the surface of spherical alumina. This addresses the problems of high interfacial thermal resistance and deteriorated mechanical properties between traditional thermally conductive fillers and epoxy resins, achieving a balance between high thermal conductivity and high strength. This invention utilizes interfacial polymerization and, through polydopamine encapsulation and synergistic metal ion complexation, constructs a catalytic curing mechanism. A metal ion-complexed polydopamine functional layer is built on the surface of polyurea microcapsules, solving the problems of single function and slow curing speed after release in existing microcapsule curing agents. This achieves an integrated function of isolation, release, and catalysis, significantly shortening the room temperature curing time. In this invention, the polydopamine layer not only provides metal ion complexation sites, but its catechol groups also have strong coordination adhesion to the metal flange substrate, further enhancing the bonding strength and forming a double bonding reinforcement effect. This invention uses cashew phenol aldehyde amine as the core curing agent. The flexible long-chain alkyl group of cashew phenol imparts excellent flexibility and water resistance to the curing system, while its high reactivity ensures rapid curing characteristics. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0021] In the following preparation examples, embodiments, and comparative examples: the bisphenol A type epoxy resin is E-51 with an epoxy equivalent of 184 g / eq; the diluent is butyl glycidyl ether; the polyurethane toughening agent is YP-50S; the fumed silica is AEROSIL R972; and the paraformaldehyde has a formaldehyde content of ≥95%.
[0022] Preparation Example 1: Step A1: 50 g each of spherical α-alumina with average particle sizes of 5 μm and 30 μm were ultrasonically dispersed in 300 mL of 95% (v / v) aqueous ethanol solution; 3 g of γ-methacryloxypropyltrimethoxysilane was added, the pH was adjusted to 4.0 with acetic acid, and the mixture was stirred at 60 °C for 4 h; the mixture was filtered, washed with ethanol, and vacuum dried at 80 °C to obtain surface-grafted alumina powder.
[0023] Step A2: Mix 0.8 g of sodium dodecyl sulfate, 80 g of alumina powder obtained in step A1, and 150 mL of deionized water, disperse by ultrasonication, and heat to 80°C; then add a mixture of 6.5 g of methacrylic acid, 13 g of butyl acrylate, 2 g of glycidyl methacrylate, and 0.2 g of ammonium persulfate, and react for 2 h; cool to room temperature, demulsify, filter, wash with deionized water, and vacuum dry at 60°C to obtain the composite thermally conductive filler.
[0024] Preparation Example 2: Compared with Preparation Example 1, the amount of methacrylic acid in step A2 was adjusted to 5 g, and the amount of butyl acrylate was adjusted to 10 g, while the other steps remained the same.
[0025] Preparation Example 3: Compared with Preparation Example 1, the amount of methacrylic acid in step A2 was adjusted to 8 g, and the amount of butyl acrylate was adjusted to 16 g, while the other steps were the same.
[0026] Comparative preparation example 1: Compared with preparation example 1, step A1 is omitted, while other steps are the same.
[0027] Comparative Preparation Example 2: Compared to Preparation Example 1, step A2 was omitted, and the product obtained in step A1 was used directly as the filler.
[0028] Preparation Example 4: Step B1: Mix 100 g of cashew phenol and 11 g of isophorone diamine, stir at 80°C and add 72 g of paraformaldehyde, heat to 95°C and react for 3 h, then distill under reduced pressure at 120°C until no water evaporates to obtain cashew phenol aldehyde amine curing agent.
[0029] Step B2: Mix 1.5 g of Span-85 and 50 g of liquid paraffin, and stir at 400 rpm for 15 min at room temperature. Add 4.5 g of cashew phenol amine curing agent and 0.05 g of methyl p-toluenesulfonate obtained in Step B1, and emulsify at 1200 rpm for 10 min to obtain an emulsion. Simultaneously, mix 1 g of hexamethylene diisocyanate and 2.5 g of liquid paraffin, and stir at 300 rpm for 10 min at room temperature. Add the hexamethylene diisocyanate mixture dropwise to the emulsion, react at room temperature for 1 h, then raise the temperature to 55℃ and continue the reaction for 5 h. Wash repeatedly with cyclohexane, filter, and air dry to obtain polyurea microcapsules.
[0030] Step B3: Polyurea microcapsules were ultrasonically dispersed in a dopamine hydrochloride solution with a concentration of 2 g / L and a pH of 8.5. The mixture was stirred at 120 rpm for 12 h at room temperature, filtered, washed with deionized water, and dried to obtain polydopamine-coated microcapsules. These microcapsules were then immersed in a 0.15 mol / L zirconium oxychloride octahydrate aqueous solution with a pH of 4, stirred at room temperature for 2 h, washed with deionized water, and vacuum dried to obtain the microcapsule curing agent.
[0031] Preparation Example 5: Compared to Preparation Example 4, the metal ion solution in step B3 was replaced with a zinc acetate aqueous solution with a concentration of 0.18 mol / L, while the other steps were the same.
[0032] Preparation Example 6: Compared to Preparation Example 4, the amount of cashew phenol amine curing agent in step B2 was adjusted to 4.0 g, and the other steps were the same.
[0033] Preparation Example 7: Compared to Preparation Example 4, the amount of cashew phenol amine curing agent in step B2 was adjusted to 5.0 g, while the other steps remained the same.
[0034] Comparative Preparation Example 3: Compared to Preparation Example 4, step B3 was omitted, and the polyurea microcapsules obtained in step B2 were used directly as curing agents.
[0035] Comparative Preparation Example 4: Compared to Preparation Example 4, only polydopamine coating was performed in step B3, without metal ion complexation treatment.
[0036] Example 1: Weigh the following raw materials by weight: Component A: 100 parts of bisphenol A type epoxy resin, 15 parts of diluent, 16 parts of polyurethane toughening agent, 170 parts of composite thermally conductive filler of Preparation Example 1, 2 parts of γ-methacryloyloxypropyltrimethoxysilane coupling agent, and 2 parts of fumed silica.
[0037] Component B: 60 parts of the microcapsule curing agent of Preparation Example 4, 12 parts of diluent, and 1 part of fumed silica.
[0038] Step S1: Add bisphenol A type epoxy resin, diluent, polyurethane toughening agent and silane coupling agent to a kneader, stir and knead for 30 min at 70℃ and vacuum degree of -0.08 MPa; then add composite thermally conductive filler, knead at 80℃ for 90 min; after discharge, grind, then add fumed silica, and degas under vacuum for 30 min to obtain component A.
[0039] Step S2: Combine the microcapsule curing agent, diluent and fumed silica and stir for 30 min, then vacuum degas for 15 min to obtain component B. During the stirring process, control the material temperature to not exceed 35℃.
[0040] Example 2: Compared to Example 1, the composite thermally conductive filler of Preparation Example 1 in component A was replaced with the composite thermally conductive filler of Preparation Example 2, and everything else remained the same.
[0041] Example 3: Compared to Example 1, the composite thermally conductive filler of Preparation Example 1 in component A was replaced with the composite thermally conductive filler of Preparation Example 3, and everything else remained the same.
[0042] Example 4: Compared to Example 1, the microcapsule curing agent in component B of Preparation Example 4 was replaced with the microcapsule curing agent of Preparation Example 5, and everything else remained the same.
[0043] Example 5: Compared to Example 1, the microcapsule curing agent in component B of Preparation Example 4 was replaced with the microcapsule curing agent of Preparation Example 6, and everything else remained the same.
[0044] Example 6: Compared to Example 1, the microcapsule curing agent in component B of Preparation Example 4 was replaced with the microcapsule curing agent of Preparation Example 7, and everything else remained the same.
[0045] Example 7: Compared to Example 1, the amount of composite thermally conductive filler in component A was adjusted to 140 parts, while other aspects remained the same.
[0046] Example 8: Compared to Example 1, the amount of composite thermally conductive filler in component A was adjusted to 200 parts, while other aspects remained the same.
[0047] Example 9: Compared to Example 1, the amount of microcapsule curing agent in component B was adjusted to 50 parts, while other aspects remained the same.
[0048] Example 10: Compared to Example 1, the amount of microcapsule curing agent in component B was adjusted to 65 parts, while other aspects remained the same.
[0049] Comparative Example 1: Compared to Example 1, the composite thermally conductive filler in component A was replaced with the product of Comparative Preparation Example 1, and everything else remained the same.
[0050] Comparative Example 2: Compared to Example 1, the composite thermally conductive filler in component A was replaced with the product of Comparative Preparation Example 2, and everything else remained the same.
[0051] Comparative Example 3: Compared to Example 1, the microcapsule curing agent in component B was replaced with the product of Comparative Preparation Example 3, and everything else was the same.
[0052] Comparative Example 4: Compared to Example 1, the microcapsule curing agent in component B was replaced with the product of Comparative Preparation Example 4, and everything else was the same.
[0053] Comparative Example 5: The cashew phenol amine curing agent prepared in Example 4 was used directly as component B in combination with component A without microencapsulation. Component A was the same as in Example 1. The formulation of component B was: 35 parts cashew phenol amine curing agent, 11 parts diluent, and 1 part fumed silica.
[0054] Take the A and B components prepared in each example and comparative example, mix them at a weight ratio of A to B of 100:30 and stir evenly. Apply the mixture to the space between carbon steel flanges that have been sandblasted and rust-removed or to the fiberglass cloth. Control the thickness of the adhesive layer to 0.3-0.5 mm and tighten it. After curing at room temperature for 24 hours, perform performance tests. 1) Pot life: Refer to GB / T 7123.1, the time required for the viscosity of the mixed adhesive to reach twice the initial value at 25℃, measured using a rotational viscometer; 2) Surface drying time: Measured at 25℃ and 50% relative humidity, in accordance with GB / T 1728; 3) Complete curing time: The time required for the residual heat of reaction to be less than 5%, as determined by DSC, at 25°C; 4) Thermal conductivity: The thermal conductivity of the cured film was measured at 25°C using a thermal conductivity meter based on ASTM E1530. 5) Shear strength: Refer to GB / T 7124, use a universal testing machine to determine the shear strength of carbon steel / carbon steel lap joint at 25℃, with a tensile rate of 5 mm / min; 6) Peel strength: Refer to GB / T 7122 to determine the T-type peel strength; 7) Storage stability: Components A and B were sealed and stored in an oven at 40°C for 30 days. The viscosity change rate was measured and whether stratification and sedimentation occurred were assessed. The test results are shown in the table below: Table 1. Detection Results of Examples
[0055] Table 2 Comparative Test Results
[0056] Based on the test results in the table, the performance of the examples and comparative examples was analyzed: Compared with Example 1, in Examples 2 and 3, methacrylic acid provides carboxyl functional groups in the polymer shell. When the amount of methacrylic acid is too low, the carboxyl density of the shell decreases, the chemical bonding sites between the filler and the epoxy matrix decrease, the interfacial thermal resistance increases, and both the thermal conductivity and shear strength decrease. When the amount of methacrylic acid is too high, the excess carboxyl groups may consume too many epoxy groups during the curing process, resulting in a decrease in crosslinking density and a slight decrease in shear strength. This indicates that the amount of methacrylic acid is one of the key factors determining the degree of chemical bonding at the filler / matrix interface, and it needs to be controlled within an appropriate range to balance the interfacial bonding density and the integrity of the crosslinking network.
[0057] Compared to Example 1, Example 4 replaced zirconium with zinc in the microcapsule curing agent. Zinc ions have weaker Lewis acidity than zirconium ions and slightly lower catalytic activity for epoxy ring-opening polymerization, thus prolonging the complete curing time. However, the zinc-complexed polydopamine layer still provides good substrate adhesion, with shear strength and peel strength slightly lower than in Example 1, but the reduction is limited. This indicates that both zirconium and zinc ions can be used in the microcapsule curing agent system of this invention; zirconium ions are superior in catalytic efficiency, while zinc ions have advantages in cost and biosafety.
[0058] Compared to Example 1, Examples 5 and 6 show that the amount of core curing agent directly affects the core-to-wall ratio of the microcapsules. A low core-to-wall ratio results in insufficient curing agent and a long curing time, while a high core-to-wall ratio results in a shorter curing time but still an acceptable pot life. This indicates that the amount of core curing agent needs to be controlled within a certain range to ensure the storage integrity and release efficiency of the microcapsules.
[0059] Compared to Example 1, in Examples 7 and 8: when the amount of composite thermally conductive filler is reduced, the density of the thermal conduction pathway decreases, and the thermal conductivity decreases; however, the viscosity of the adhesive decreases, wettability improves, and shear strength and peel strength are actually improved. When the amount of filler is increased, the thermal conductivity increases, but the viscosity of the adhesive increases significantly, wettability decreases, shear strength decreases, and storage stability also deteriorates. This indicates that the amount of filler is a key factor determining the balance between thermal conductivity and mechanical properties.
[0060] Compared to Example 1, Examples 9 and 10 show the following differences: When the amount of microcapsule curing agent is reduced, the effective curing agent is insufficient, the complete curing time is prolonged, and the shear strength is slightly reduced. When the amount is increased, the curing reaction is more complete, the crosslinking density is higher, and the complete curing time is shortened. However, excessive microcapsule wall material residue may become defect points, and the peel strength is slightly reduced. This indicates that the amount of microcapsule curing agent needs to be controlled within an appropriate range to ensure a balance between curing effect and mechanical properties.
[0061] Comparative Example 1 compared to Example 1: Comparative Example 1 replaced the composite thermally conductive filler with the product of direct emulsion polymerization of untreated alumina. Because the alumina surface lacks polymerizable double bonds, the methacrylate copolymer could not be grafted onto the alumina surface via covalent bonds, existing only as physically adsorbed or as independent latex particles. During curing, there was no chemical bond between the polymer shell and the alumina, resulting in a weak interface layer at the filler / matrix interface. Furthermore, the unmodified alumina exhibited poor dispersion stability in component A, showing significant sedimentation during storage. This clearly demonstrates the crucial role of silane coupling agent anchoring treatment in ensuring the chemical bonding and dispersion stability of the filler / matrix.
[0062] Compared to Example 1, Comparative Example 2 only underwent silane coupling agent surface treatment without emulsion polymerization coating. The alumina surface only contained methacryloyloxy groups, lacking the interfacial stress buffering effect of an elastomeric shell. Under stress, the modulus mismatch between the rigid alumina and the epoxy matrix led to stress concentration, resulting in a significant decrease in both shear strength and peel strength. Simultaneously, the thermal conductivity was slightly lower than in Example 1. This clearly demonstrates the necessity of an elastomeric shell for simultaneously improving both thermal conductivity and mechanical properties.
[0063] Comparative Example 3 compared to Example 1: Comparative Example 3 directly used polyurea microcapsules. Because the polyurea microcapsules have a smooth surface, poor compatibility with epoxy resins, and are chemically inert compared to the microcapsules of Example 1, they lack catalytic function. This resulted in a prolonged complete curing time and reduced shear strength and peel strength. This clearly demonstrates the crucial role of the polydopamine layer and its complexed metal ions in improving curing speed and bond strength.
[0064] Comparative Example 4 compared to Example 1: Comparative Example 4 underwent polydopamine coating but did not complex with metal ions. The polydopamine layer provided substrate adhesion for the catechol groups, and the peel strength was improved compared to Comparative Example 3, but the complete curing time was still significantly longer than that of Example 1. This is because it lacked a Lewis acid catalyst to accelerate the ring-opening of epoxy groups. This indicates that metal ion complexation is the core mechanism that endows the microcapsule curing agent with catalytically accelerated curing function.
[0065] Compared to Example 1, Comparative Example 5 used cashew phenol amine curing agent directly as component B without microencapsulation. After mixing components A and B, the curing agent reacted immediately with the epoxy resin, resulting in a short pot life that could not meet the time requirements for flange bonding. Although the curing speed was fast, it was an uncontrollable instantaneous curing process; the adhesive did not have enough time to fully wet the substrate surface before gelling, leading to a decrease in bond strength. This fully demonstrates the necessity of microencapsulation for achieving a balance between long pot life and fast curing.
[0066] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A two-component, fast-curing adhesive for flange assembly, comprising component A and component B, characterized in that, By weight: The A component comprises: 100 parts of bisphenol A type epoxy resin, 15 parts of diluent, 16 parts of polyurethane toughening agent, 140-200 parts of composite thermally conductive filler, 2 parts of silane coupling agent, and 2 parts of fumed silica. Component B comprises: 50-65 parts of microcapsule curing agent, 12 parts of diluent, and 1 part of fumed silica. The composite thermally conductive filler is prepared by the following steps: Step A1: Spherical α-alumina with an average particle size of 5 μm and spherical α-alumina with an average particle size of 30 μm are mixed at a mass ratio of 1:1 and ultrasonically dispersed in a 95% (v / v) aqueous ethanol solution. γ-methacryloyloxypropyltrimethoxysilane is added, and the pH is adjusted to 4.0 with acetic acid. The mixture is stirred at 60°C for 4 h, filtered, washed with ethanol, and vacuum dried at 80°C to obtain surface-grafted alumina powder. Step A2: Sodium dodecyl sulfate, surface-grafted alumina powder and deionized water are mixed, ultrasonically dispersed and heated to 80°C. Then a mixture of methacrylic acid, butyl acrylate, glycidyl methacrylate and ammonium persulfate is added. The mixture is reacted for 2 h, cooled to room temperature, demulsified, filtered, washed with deionized water and vacuum dried at 60°C to obtain the composite thermally conductive filler. The microcapsule curing agent is prepared by the following steps: Step B1: Mix cashew phenol and isophorone diamine, stir at 80°C and add paraformaldehyde, heat to 95°C and react for 3 hours, then distill under reduced pressure at 120°C to obtain cashew phenol aldehyde amine curing agent. Step B2: Span-85 and liquid paraffin were mixed and stirred at 400 rpm for 15 min at room temperature. Cashew phenol amine curing agent and methyl p-toluenesulfonate were then added and emulsified at 1200 rpm for 10 min to obtain an emulsion. Hexamethylene diisocyanate was mixed with liquid paraffin and stirred at 300 rpm for 10 min at room temperature to obtain a mixture. The mixture was added dropwise to the emulsion and reacted at room temperature for 1 h. The temperature was then raised to 55 °C and the reaction continued for 5 h. The mixture was washed with cyclohexane and air-dried to obtain polyurea microcapsules. Step B3: Disperse polyurea microcapsules ultrasonically in dopamine hydrochloride solution, stir at room temperature and 120 rpm for 12 h, filter, wash with deionized water, and dry to obtain polydopamine-coated microcapsules; immerse the polydopamine-coated microcapsules in a metal ion solution, stir at room temperature for 2 h, wash with deionized water, and dry to obtain microcapsule curing agent.
2. The two-component, fast-curing adhesive for flange assembly according to claim 1, characterized in that: In step A1, the ratio of the total mass of alumina, γ-methacryloxypropyltrimethoxysilane, and aqueous ethanol solution is 100g:3g:300mL.
3. The two-component, fast-curing adhesive for flange assembly according to claim 1, characterized in that: In step A2, the ratio of sodium dodecyl sulfate, surface-grafted alumina powder, deionized water, methacrylic acid, butyl acrylate, glycidyl methacrylate, and ammonium persulfate is 0.8g:80g:150mL:5-8g:10-16g:2g:0.2g.
4. The two-component, fast-curing adhesive for flange assembly according to claim 1, characterized in that: In step B1, during the preparation of the cashew phenol aldehyde amine curing agent, the ratio of cashew phenol, isophorone diamine, and paraformaldehyde is 10g:1.1g:7.2g.
5. The two-component, fast-curing adhesive for flange assembly according to claim 1, characterized in that: In step B2: during the emulsion preparation process, the ratio of Span-85, liquid paraffin, cashew phenol amine curing agent and methyl p-toluenesulfonate is 1.5g: 50g: 4-5g: 0.05g; during the mixture preparation process, the ratio of hexamethylene diisocyanate to liquid paraffin is 1g: 2.5g.
6. The two-component, fast-curing adhesive for flange assembly according to claim 1, characterized in that: In step B3: the dopamine hydrochloride solution has a mass concentration of 2 g / L and a pH of 8.5; the metal ion solution is either a zinc ion solution or a zirconium ion solution. When using a zirconium ion solution, the concentration is 0.15 mol / L of zirconium oxychloride octahydrate aqueous solution with a pH of 4; when using a zinc ion solution, the concentration is 0.18 mol / L of zinc acetate aqueous solution.
7. A method for preparing a two-component, fast-curing adhesive for flange assembly as described in any one of claims 1-6, characterized in that, The process includes the following steps: Step S1: Bisphenol A type epoxy resin, diluent, polyurethane toughening agent and silane coupling agent are added to a kneader and kneaded for 30 min at 70°C and a vacuum degree of -0.08 MPa; then composite thermally conductive filler is added and kneaded for 90 min at 80°C; after discharge, the mixture is ground and then fumed silica is added and vacuum degassing is performed for 30 min to obtain component A; Step S2: Combine the microcapsule curing agent, diluent and fumed silica and stir for 30 min, then vacuum degas for 15 min to obtain component B. During the stirring process, control the material temperature to not exceed 35℃.
Citation Information
Patent Citations
High-thermal-conductivity and high-temperature-resistant epoxy resin pouring sealant with cold and hot impact resistance
CN120041124A
High-temperature-resistant tough epoxy resin adhesive and preparation method thereof
CN121227258A